New Italian migrations to the United States. - Ruberto, Laura E.; Sciorra, Joseph; Tamburri, Anthony Julian (University of Illinois Press, 2017)
"This project, edited by Joseph Sciorra and Laura Ruberto, reevaluates the political, social, and cultural significance of Italian emigration to the U.S. since World War II. Particular areas of focus are community (urban and suburban) development, politics and economics, transnationalism, the media, group identity, and expressive culture. Contributors provide critical interventions on the relationships new immigrants created with established Italian American communities, including both the primarily working class migrants in the immediate postwar period and the new professional class of migrants who began to arrive in the 1970s. The volume also assesses more generally how ongoing European migration is related to postmodern notions of white ethnicity, thus advancing conversations about the complex understanding of U.S. white ethnicity as multivalent, unstable, and at times contradictory, rather than as a fixed historical process that leads to white privilege and ethnic assimilation"--